2019
DOI: 10.1101/727859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic age is accelerated in schizophrenia with age- and sex-specific effects and associated with polygenic disease risk

Abstract: Schizophrenia (SCZ) is a severe mental illness that is associated with an increased prevalence of age-related disability and morbidity compared to the general population. An accelerated aging process has therefore been hypothesized as a component of the SCZ disease trajectory. Here, we investigated differential aging using three DNA methylation (DNAm) clocks (i.e. Hannum, Horvath, Levine) in a multi-cohort SCZ whole blood sample consisting of 1,100 SCZ cases and 1,200 controls. It is known that all three DNAm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
1
9
2
Order By: Relevance
“…We found that epigenetic age was significantly accelerated by +2.3 year in schizophrenia patients as compared to healthy controls for the PhenoAge clock, but not for the DNAmAge clock. Previous reports suggest no accelerated epigenetic aging or association with premature mortality for schizophrenia in blood or post-mortem brain samples (McKinney et al, 2017; Voisey et al, 2017; McKinney et al, 2018; Kowalec et al, 2019), with some exceptions (Okazaki et al, 2019; Ori et al, 2019; Higgins-Chen, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We found that epigenetic age was significantly accelerated by +2.3 year in schizophrenia patients as compared to healthy controls for the PhenoAge clock, but not for the DNAmAge clock. Previous reports suggest no accelerated epigenetic aging or association with premature mortality for schizophrenia in blood or post-mortem brain samples (McKinney et al, 2017; Voisey et al, 2017; McKinney et al, 2018; Kowalec et al, 2019), with some exceptions (Okazaki et al, 2019; Ori et al, 2019; Higgins-Chen, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Subjects included in this study were part of two longitudinal schizophrenia cohorts (van Haren et al, 2007; Boos et al, 2012). Brain age in these cohorts has been described before (Schnack et al, 2016) and these cohorts were part of a study on epigenetic aging in schizophrenia (Ori et al, 2019). Here we included unrelated subjects that had imaging data and either epigenetic or genetic data available, resulting in a dataset of 411 unrelated subjects (193 cases, 218 controls, 36% female) of European descent spanning a wide range of the adult lifespan (mean = 32.7 years, range = [16.7 - 67.5] at baseline).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we performed separate meta-analyses of peripheral blood collected after birth (N=14,434) and cord blood (N=2,425), followed by a combined meta-analysis (N=15,324) including an examination of heterogeneity of effects. Next, we tested the relationship between aggressive behavior and epigenetic clocks, as associations of lifetime stress , exposure to violence 25 , and psychiatric disorders 26,27 with accelerated epigenetic ageing have been reported. We performed extensive functional follow-up by integrating our findings with data on gene expression, mQTLs and DNA methylation in brain samples.…”
Section: Introductionmentioning
confidence: 99%